Functional and Morphological Development of the Womb Throughout Life. (June 2015) - Sheldon, Rachel E.; Shmygol, Anatoly; Van Den Berg, Hugo A.; Blanks, Andrew M.
The uterus undergoes changes throughout a woman's life, beginning with her own embryonic development when she is still in the womb, commencing a monthly cycle at the onset of adulthood, and undergoing dramatic changes during pregnancy and parturition. The impact of preterm labour and other perinatal health problems is significant, both in human and financial terms; therefore the study of the physiological and regulatory changes which the uterus undergoes can be of enormous potential benefit. Here we briefly review the current state of knowledge, with an emphasis on the importance of changes in connectivity in the uterine smooth muscle cell network and on recent mathematical modelling work aimed at elucidating the role of spatial heterogeneity in this connected network.